Factors Affecting the Benefits of Recipients of Round Pond Assistance in Hulu Sungai Tengah Regency, South Kalimantan Province - MUHAMAD RAMLI; Achmad Syamsu Hidayat; Idiannor Mahyudin (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
The round pond assistance program in Hulu Sungai Tengah Regency is an initiative by the Food Security and Fisheries Service (DKPP) to improve community welfare, especially extreme poor groups. This study aims to (1) analyze the characteristics of round pond assistance recipients and (2) analyze the factors affecting the profits of round pond assistance recipients in Hulu Sungai Tengah Regency. The research method used was a mixed method with 50 respondents selected by purposive sampling. Data were analyzed using descriptive analysis and multiple linear regression. The results showed that recipient characteristics were dominated by males (96%), aged 46-60 years (60%), with elementary education (64%), minimal aquaculture experience (<1 year, 96%), and working as farmers/planters (72%). Partially, only the training variable had a significant effect on profit (<0.001), while age, education, aquaculture experience, gender, and occupation did not have a significant effect. Simultaneously, all variables had a significant effect on profit (0.004). The R² value of 0.351 indicates that the model can explain 35.1% of profit variation. Training is the key factor in increasing the profits of round pond fish aquaculture.